Company's financial condition, debt default, and audit committee on defending going concern: springate model & financial company - Orlin Cicilia (SEAN Institute, 2024)
Going concern has become a phenomenon and must be obeyed by companies, especially for a company registered as a go public company. Because the impact of the going concern is meaningful which it not only makes the company have a long life for its existence in the marketplace, but also can attract new investors to invest at the company. This research is studied to know the analysis of the effect of financial condition and debt default on going concern. The sampling method used is purposive sampling method with special requirements or criteria of sample which are 60 financial institution companies listed on the IDX (Indonesia Stock Exchange) in 2015-2018. This research uses IBM SPSS 21.0 program and variety of journals and references relating to the topic of the research as well as other information from legal websites on the internet. The results of this study show that both financial condition and debt default don't have an effect on going concern with the audit committee as a control variable.